Caracterização microestrutural e propriedades de desgaste de revestimento de aço inoxidável supermartensítico modificado com boro processado por HVOF - Santos, Lucas da Silva (Universidade Federal de São Carlos, 2019)
Stainless steels are recognized as good materials to be used in corrosive environments, but their wear resistance does not exhibit good results. Therefore, researches have been developed to increase the wear resistance of stainless steels by the addition of boron. Significant improvements in wear resistance were obtained by the addition of boron in the supermartensitic stainless steels processed by spray forming due to the formation of hard M2B borides in the microstructure. This work has the objective the production of HVOF (High Velocity Oxygen Fuel) coatings of the modified supermatensitic steel with 0.7% wt. of boron (SM-14Cr-0.7B), its microstructural characterization and evaluation of the wear properties. The coatings were produced manually using powders in two distinct particle sizes, 0-20 μm and 20-53 μm. The powders and coatings were characterized by optical microscopy (OM), scanning electron microscopy (SEM), X-ray diffraction (XRD). The two particle sizes presented microstructures composed of martensite, retained austenite and M2B type borides. The coating obtained with powders of 20-53 μm granulometry presented in its microstructure a small amount of oxides and borides of type M2B in two forms: coarser borides in the form of a three-dimensional network interconnected; and in the form of spherical precipitates of the order of 100 nm or less distributed within the martensitic matrix. The coating obtained by the powders of 0-20 μm granulometry presented a low average thickness and a high amount of oxides. The wear rate obtained by the pin-on-disc test for the SM-14Cr-0.7B coating processed by HVOF using the powders of particle size 20-53 μm was approximately one order of magnitude lower than that obtained for AISI 1010 steel and unmodified supermartensitic steel.
Micro-structural characterization of supermartensitic stainless steel coating modified with boro processed by HVOF
Keywords: Caracterização microestrutural; Aço supermartensítico; HVOF; Microstructural characterization; Supermartensitic steel; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::METALURGIA FISICA